Microstructural and textural evolution of calcite deformed to high shear strain by high-pressure torsion. (January 2019) - Schuster, Roman; Habler, Gerlinde; Schafler, Erhard; Abart, Rainer
Abstract: Calcite powder aggregates were deformed to shear strains up to 80 by high-pressure torsion at temperatures of 235 and 450 °C and confining pressures of 1–4 GPa. At 235 °C the deformation occurs by twinning and limited dislocation creep as well as by brittle processes. In contrast, subgrain rotation recrystallization is the predominant deformation mechanism at 450 °C. The high confining pressures affect the microstructural evolution by inhibiting crack nucleation and propagation and by constraining the mobility of point defects. While at 1.2 GPa confining pressure transient core-mantle microstructures are produced for all strain-rates, the recrystallization is strain-rate dependent at 2–4 GPa confining pressure. Core-mantle microstructures are produced at high strain-rates, whereas the porphyroclasts deform more homogeneously at low strain rates. This change in microstructural evolution is ascribed to the phase transition from calcite to CaCO 3 -II at 1.6 GPa. Within the stability field of CaCO 3 -II an increase in the confining pressure leads to reduction of the recrystallized grain size. Irrespective of the confining pressure a strong crystallographic preferred orientation is developed during deformation at 450 °C, which is compatible with dislocation glide on the r { 10 1 ¯ 4 } 〈 2 ¯ 021 〉 slip systems. Highlights: HPT allows for deformation of calcite to very high strains even at low temperatures. HPT processing of calcite leads to subgrain rotation recrystallization at 450 °C. At 450 °C high pressure polymorphs affect transient recrystallization microstructures. The size distribution of recrystallized grains is pressure dependent at 450 °C. At 450 °C a pronounced texture compatible with slip on r{1014}‹2021› develops.